Abiotic Soil Health Indicators that Respond to Sustainable Management Practices in Sugarcane Cultivation - Farhate, Camila Viana Vieira [UNESP]; Souza, Zigomar Menezes de; Cherubin, Mauricio Roberto; Lovera, Lenon Herique; Oliveira, Ingrid Nehmi de; Carneiro, Marina Pedroso; La Scala Jr., Newton [UNESP] (Mdpi, 2020)
Soil quality (SQ) assessments are fundamental to design more sustainable land uses and management practices. However, SQ is a complex concept and there is not a universal approach to evaluate SQ across different conditions of climate, soil, and cropping system. Large-scale sugarcane production in Brazil is predominantly based on conventional tillage and high mechanization intensity, leading to SQ degradation. Thus through this study, we aim to assess the impact of sustainable management practices, including cover crops and less intensive tillage systems, in relation to the conventional system, using a soil quality index composed of abiotic indicators. Additionally, we developed a decision tree model to predict SQ using a minimum set of variables. The study was conducted in the municipality of Ibitinga, Sao Paulo, Brazil. The experimental design used was in strips, with four cover crops and three tillage systems. We evaluated three sugarcane cultivation cycles (2015/16, 2016/17, and 2017/18 crops). To calculate the SQ index, we selected five abiotic indicators: macroporosity, potassium content, calcium content, bulk density, and mean weight-diameter of soil aggregates. Based on our SQ index, our findings indicated that the soil quality was driven by the production cycle of sugarcane. Although a reduction of soil quality occurs between the plant cane and first ratoon cane cycles, from the second ratoon cane there is a trend of the gradual restoration of soil quality due to the recovery of both the soil's physical and chemical attributes. Our study also demonstrated that the cultivation of sunn hemp and millet as cover crops, during the implementation of sugarcane plantation, enhanced soil quality. Due to the advantages provided by the use of these two cover crops, we encourage more detailed and long-term studies, aiming to test the efficiency of intercropping involving sunn hemp and millet during the re-planting of sugarcane.
Keywords: soil health management; minimum data set; principal component analysis; sustainable management; data mining